2021
DOI: 10.1370/afm.2642
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of US Youth During Initial Month of the COVID-19 Pandemic

Abstract: PURPOSE Asymptomatic youth in the United States acting as "silent spreaders" during the coronavirus disease 2019 (COVID-19) pandemic are an ongoing public health concern, particularly given their depiction as unengaged with recommendations. Our goal was to understand the knowledge, beliefs, and experiences of US youth at the onset of the COVID-19 pandemic. METHODS We posed 2 open-ended surveys to the national MyVoice text message cohort of youth, aged 14-24 years. On March 6, 2020, 4 questions were asked regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…This was in concordant with Coroiu et al study, in which 84% of the participants were of the opinion" I feel a sense of responsibility to protect our community". Waselewski et al found evidence in their survey that people believing covid-19 as the biggest threat to the society in our time had an intent to practice more social distancing 13,18 .…”
Section: Discussionmentioning
confidence: 86%
“…This was in concordant with Coroiu et al study, in which 84% of the participants were of the opinion" I feel a sense of responsibility to protect our community". Waselewski et al found evidence in their survey that people believing covid-19 as the biggest threat to the society in our time had an intent to practice more social distancing 13,18 .…”
Section: Discussionmentioning
confidence: 86%
“…This cohort represents about 15% of practice A outpatients (4.5% aged <5 years, 4.8% aged 5–11 years, 4.9% aged 12–17 years), so these findings should be interpreted cautiously, though national trend analyses from this study period also showed higher case incidence in adolescents than in younger children [ 16 ]. As communities reopen, and children and adolescents continue to interact through school, recreational activities, and other social gatherings, the COVID-19 pandemic presents unique challenges in navigating and prioritizing social interactions, particularly among adolescents who often exercise independent decision-making [ [17] , [18] , [19] ]. Families might benefit from communication focused on reducing SARS-CoV-2 transmission during holidays.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents quickly embraced social distancing and hand washing and expressed concern for the welfare of others, an important sign of maturity. 31 Data from the Centers for Disease Control and Prevention showed that 52% of adolescents aged 13-17 years would choose vaccination. 32 Thousands gave their consent/assent (along with parental consent) to participate in clinical trials, with sharing of essential information including safety, efficacy, risk, side effects, and the purpose of the study.…”
Section: Capacity To Consent To Covid-19 Vaccinationmentioning
confidence: 99%